2010
DOI: 10.1121/1.3533839
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Classroom Acoustics on the Voice Levels of Teachers With and Without Voice Problems: A Field Study

Abstract: Many teachers suffer from voice problems and classroom acoustics has been considered as one of the potential hazards for this. The present study examines how classroom acoustics interacts with the voices of 14 teachers without voice problems and 13 teachers with voice problems. The assessment of the voice problems was made with a questionnaire and a laryngological examination. During teaching, the sound pressure level at the teacher's position was monitored. The teacher's voice level and the activity noise lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…[22] Finally, one must also realize that the RT is a crude acoustical parameter, and that other parameters such as clarity or the ratio between early and late sound reflections may turn out to be more relevant in characterizing and optimizing school teachers' acoustical working environment. Yet, since the RT often is correlated with other acoustical parameters it represents a feasible choice, as for example, verified by its use in a contemporary building regulations.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Finally, one must also realize that the RT is a crude acoustical parameter, and that other parameters such as clarity or the ratio between early and late sound reflections may turn out to be more relevant in characterizing and optimizing school teachers' acoustical working environment. Yet, since the RT often is correlated with other acoustical parameters it represents a feasible choice, as for example, verified by its use in a contemporary building regulations.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous investigation, the same teachers were studied in a real teaching scenario. 21 Although the results of that study were problematic from the methodological perspective, because most of the individuals talked in just one environment, the group-wise differences were statistically significant. It is possible that teachers perceived the laboratory scenario as non-demanding and did not stress their voices as if it was a real teaching situation.…”
Section: B Effect Of Voice Healthmentioning
confidence: 90%
“…It is possible that teachers with more severe voice symptoms limit their voice use more than teachers with healthier voices. This is achieved by using lower voice SPL [25] and less raising of F 0 [15]. Our results showed that the more mucus there was in the participant’s throat, the higher F 0 she used during the first lesson.…”
Section: Discussionmentioning
confidence: 76%
“…Both studies report 9 dB higher values for activity noise level than the present study. The explanation for the different results may be that in those 2 studies all lessons were recorded, not specifically lessons in core subjects and, furthermore, leisure time was also included in most of the recordings by Södersten et al Other possible reasons for the differences may be variation in pedagogical methods [24], in the subjects addressed in the lessons [2], or in the acoustics of the classroom [25]. Furthermore, variations in time window settings may have also influenced the differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation